Modified French Osteotomy for Cubitus Varus Correction – Our Experience - P. Madhuchandra; K. M. Pawankumar (Journal of Orthopedics, Traumatology and Rehabilitation)
Background: Various fixation techniques have been described for the osteotomy for correction of cubitus varus. K-wiring was used in the past for fixation. However, rates of fixation failure and pin-track infection were high. Fixation with two screws and a figure-of-eight wiring provides a stable fixation in children younger than 15 years. We used a modified lateral approach and figure-of-eight construct with two screws and evaluated the outcome of the results. Materials and Methods: Thirty-five patients out of the total 54 patients who underwent modified French osteotomy between January 2013 and December 2021 were evaluated in a retrospective manner. Patients were evaluated using the modified Mayo elbow performance scoring system. Results: There were 22 males and 13 females in the study group. We had excellent results in 16 cases, good outcome in 13 cases and fair outcome in 6 of our cases. Superficial infection was seen in three patients and four patients had occasional negligible pain. There was no loss of correction and fixation failures in our study. Conclusion: Modified French osteotomy using two screws and figure-of-eight wiring is a simple and safe procedure that gives excellent outcomes. A careful preoperative planning, careful surgical technique, and stable fixation are key to achieve excellent and good functional outcomes.